PARADOXOS CONTEMPORÂNEOS: DESAFIOS AOS PROFESSORES - Maria Regina Clivati Capelo (Universidade do Oeste Paulista, 2005)
Under the supposition that the universe of youngsters is becoming more complex sue to the society's information process and the advance of communication, this article focus on challenges and problems that teachers are faced every day. The macro-social determination represented by media and images, other familiar arrangements, the deepening of inequalities and uncertainties, the emergence of diversities, the violence banality, among others, requires rethinking of school's social relations in order to become more coherent with the current demands. This text suggests some possible, however not conclusive, actions since this is a analytic field that requires additional research.